A CURRICULUM EVALUATION FOR GRADUATE DIPLOMA PROGRAM IN TEACHING PROFESSION (REVISED CURRICULUM, B.E. 2562) FACULTY OF EDUCATION, RAJABHAT RAJANAGARINDRA UNIVERSITY - Onkasem, Porntip; Koolnapadol, Aungkana; Sirathatnararojana, Thanyaphatx; Potjana-areewong, Jiraporn; Hunsaen, Sansern (Journal of MCU Nakhondhat, 2023)
This research aims to evaluate the Graduate Diploma Program in Teaching Profession Curriculum (Revised curriculum, B.E. 2562), Faculty of Education, Rajabhat Rajanagarindra University, by applying the CIPP assessment model and standard criteria for graduate programs B.E. 2558, which consisted of the context, fundamental factors, process, and products. The sample consisted of 5 teachers responsible for the curriculum, and 23 instructors by selective sampling, 217 alumni and current students, and 217 entrepreneurs. The sample size was determined by using Krejcie and Morgan’s table and the accidental sampling method was used. The instrument used for data collection was a curriculum evaluation form of Graduate Diploma Program in Teaching Profession (Revised Curriculum, B.E. 2562) for the teachers responsible for the curriculum, and a curriculum evaluation form of Graduate Diploma Program in Teaching Profession (Revised Curriculum, B.E. 2562) for the students. The validity was examined by analyzing the consistency of the evaluation items with the research objectives according to the opinions of experts, with a consistency between .80 - 1.00 and it was used to try out to collect data to determine suitability and possibility. Percentage, mean, and standard deviation were used for data analysis. The research findings were as follows: the opinions of teachers responsible for the curriculum, instructors, alumni and current students were consistent that the Graduate Diploma Program in Teaching Profession (Revised curriculum, B.E. 2562) in the aspects with the highest average were context, followed by products, fundamental factors, and the last aspect was the process. In terms of the further inquiry of the entrepreneurs’ opinions, it was found that the overall product aspect was at a high level in both domains, namely 1) desirable graduate characteristics, and 2) satisfaction towards work performance.